Authoritative Parenting in the Novel Ayahku (Bukan) Pembohong and Its Relevance to Literary Appreciation Learning in Senior High School - Fitroh, Aminatul Fitroh; -, Sumartini (Jurnal Bahasa Indonesia Prima (BIP), 2026)
This study aims to analyze authoritative parenting styles in the novel Ayahku (Bukan) Pembohong by Tere Liye and to examine its relevance to literary appreciation instruction in high school. This study employs a qualitative descriptive method using a literary psychology approach. The data consist of text excerpts sourced from the novel Ayahku (Bukan) Pembohong by Tere Liye. Data was collected through a reading-and-noting technique, involving a thorough and repetitive reading of the text. Data analysis utilized the Miles & Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The data was classified based on indicators of authoritative parenting according to Baumrind and then analyzed for its relevance based on aspects of instructional material selection according to Rahmanto. The findings indicate that the authoritative parenting style in the analyzed novel is characterized by dialogic communication, modeling of values, rational control, and emotional warmth, which contribute to the development of the child character’s independent, empathetic, responsible, and emotionally mature personality. Furthermore, the novel’s relevance as instructional material examined from linguistic, psychological, and cultural background perspectives has the potential to develop students’ critical and reflective thinking skills through literary appreciation courses in high school.